2012
DOI: 10.1063/1.4759153
|View full text |Cite
|
Sign up to set email alerts
|

Sign preference in ion-induced nucleation: Contributions to the free energy barrier

Abstract: We have performed a series of computer simulations using the AVUS-HR approach to better understand the origin of the sign preference in ion-induced nucleation. In particular, we emphasize the importance of distinguishing between the total formation free energy of a cluster, and the nucleation free energy, which involves only those steps contributing to the free energy barrier. We have separately considered how the ion-water potential energy, the water-water potential energy, and the entropy contribute to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…The ion–water term is also included in this figure, which is shown to be consistently unfavorable for the 3 Å ion case. Thus, the water–water term has to be significantly more favorable for this 3 Å ion, which is expected, since, for the 1 Å ion case, the much stronger ion–water interactions can be more disruptive to the hydrogen bonding between water molecules, which was also noted in previous ion-induced water nucleation studies. , …”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The ion–water term is also included in this figure, which is shown to be consistently unfavorable for the 3 Å ion case. Thus, the water–water term has to be significantly more favorable for this 3 Å ion, which is expected, since, for the 1 Å ion case, the much stronger ion–water interactions can be more disruptive to the hydrogen bonding between water molecules, which was also noted in previous ion-induced water nucleation studies. , …”
Section: Resultssupporting
confidence: 68%
“…7 However, only recently, with the development of new simulation methods and fast computer platforms, extensive simulations can be afforded to allow for more accurate assessment (and thus more meaningful interpretation) of the important features related to the NFE profiles and other thermodynamic properties of the clusters. For example, Keasler et al 43 carried out a systematic study on both positive and negative ions of various sizes and found that the location of this precritical stable cluster holds the key to the magnitude of the overall decrease on the barrier. In addition, Vehkamaki et al 7 found that the conventional NT that has been commonly used for the extrapolation of the critical cluster size/composition from the experimentally measured rates was found to be invalid for these ion-induced systems due to the presence of this precritical stable cluster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its intensive study had started from the end of 19th century by works of Thomson, Wilson, Tohmfor, and Volmer [1][2][3] and continues today. [4][5][6] The results of last several decades of experimental studies, [7][8][9][10][11][12][13][14][15][16][17] numerical simulation, [18][19][20][21][22][23] application of the density functional methods, [24][25][26][27] as well as developing of theoretical analytical approaches [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] extended our understanding of the effects of the electric field of the charged condensation center on the critical vapor supersaturation, nucleation rates, the number of nucleating droplets, and other nucleation characteristics. However, there are still some questions in thermodynamic description of vapor nucleation on a charged dielectric nanoparticle that have to be answered.…”
Section: Introductionmentioning
confidence: 99%
“…To solve Eq. (23), we substitute the results for the electric potential ϕ α 0 and ϕ β 0 into the right-hand side of Eq (23). and represent function f as series expansions in the Legendre polynomials P n (cos θ ),…”
mentioning
confidence: 99%